Towards mitigating engine-out emissions: A migration to fuel based and combustion based solutions - Opatola, R.A. (Asian Research Publishing Network, 2016)
Road transport is a key source of ambient pollution especially in urban regions. While the moderation of engine-out emissions from road transport is seen as key in the improvement of global air quality, the overall sales of automobiles which contribute to air pollution keep rising. This trend has impelled global alertness due to the grave consequences of human exposure to air pollutants. In this light, a study was conducted to review the steps that are being taken by stakeholders in the automotive industry in contending the menace, in terms of research and development; the economy cum the suitability of the methods and devices that are being used in extenuating engine-out emissions. The study revealed that modern hardware based solutions such as high-pressure fuel injection equipment (FIE), sophisticated piezo-injectors, diesel particulate filters (DPF) and associated control systems are prevalent among the existing methods in use by engine designers and manufacturers. However, these technologies are prone to salient setbacks such as limited durability, high cost and difficulty in installing on extant engines, among others. Hence, much as the modern hardware based solutions had to offer, yet there were no one-size-fits-all solutions in place. Most of the existing solutions enjoy, at best, relative advantages over one another. Conversely, the significant revelation of this study were the plethora of prospects that the fuel based solutions and combustion based solutions could offer various stakeholders in the drive towards finding an enduring panacea to engine-out emissions. Therefore, there are room for progress in research and development toward finding sustainable solutions to the threats that engine-out emissions pose to humans and the environments. Â© 2006-2016 Asian Research Publishing Network (ARPN).